Projeto Educativo E Político-Pedagógico Da Escola De Ensino Médio: Tradições E Contradições Na Gestão E Na Formação Para O Trabalho - Ramos, Jeannette Filomeno Pouchain (2009)
The Brazilian education, founded by the logic submission of the educational project from the Jesuits, and the influences from the French, English and Americans, passed on to be considered a national problem with the proclamation of the republic in 1980. The attempt to regulate and to consolidate the social function propaedeutics, which denies the work, the industrialization who demanded the instrumental education for work and the reestablishment of the democracy in the state which reorganized the flexible production and impose the formation of a new type of worker (KUENZER, 1998) presents contradictories movements. In agreement with transformation the scientific technical conception of organization adopted participative democratic mechanism. Recognizing the contradiction in keeping distinct types of logic and the tendency of the liberal logic over the social logic, the challenger of the work management is to reverse this premise. As an alternative to the educational middle class project, the polytechnic education proposes to overcome the dual structure and history by omni lateral formation (SAVIANI, 2003). The elementary and middle school should be guided by the work as an excellent base for education (PISTRAK, 2005). The school, known as the work product of man, should be linked to school life as a social transformation combined with school education with material production and to promote self and social emancipation. In context, the general objective is to analyze the experience of reorganizing the educational work in creation of the politic pedagogic project of middle school, identifying perspectives, limits, possibilities, and resistances. The specifics objectives are to examine the evolution of the educational project in the social politic and economic history of Brazil, highlighting the management of school work and the formation of the young for work; analyze fundamentals, intentions and practices which guide the politic pedagogic project and identify and analyze the limits, possibilities and ways of group resistances in the management project. We choose as a theoretical methodological referential the Critic Theory and the method with materialistic history base. As instruments of qualitative and quantitative data collection we applied questionnaires, semi-structures interviews and focal groups. Among hypothesis should public school follow the educational project of middle class or should it follow the lines of vocational extent, instrumental; to attend to middle class project of the popular sector? The hard format of school has accomplished changes in the lines of directions? The politic pedagogic project working at Liceu do Maracanaú establish four pillars which reorganize the work in the school bearing in mind the full formation of the young. This school thinks, conceives and evaluates opposition to the others schools; it breaks with the traditional format of the work organization. The multiples intelligences are understood as principles, the project of work is the means to transformation of popular knowledge to the scientific knowledge with practice and social application of ideas in development of competencies and abilities, as means an half-yearly organizational and the evaluation as the learning observation. Scientific initiation in middle level education attends the interests of the school, highlighting the talents, improving the indicators and presenting results. This project is contradictory because the fundamentals and practice pedagogic reassures the principles of the traditional format and the process of schooling. This way the study confirms that is possible reorganize the work and this is done by the politic pedagogic project (PPP). Faced with the new demands the schools find themselves in a cross road and their functionality is placed at doubt. As a result of this, we point out the crises of education, formation of young and the society. It is necessary to invest in the contradictions of the system and take possession of them to construct another, the opposite and reverse. It is up to the intellectuals and educators to do their job.